Foreign exchange, interest and the dynamics of public debt in Latin America - Carlos E. Schonerwald da Silva; Matías Vernengo (The University of Utah, Department of Economics, 2007)
The relationship between the exchange rate and public debt is intermediated by two mechanisms. On the one hand, exchange rate devaluation implies higher payment on local currency over the debt denominated in foreign currency. On the other hand, the rise of public debt leads a perception of higher default risk, forcing capital outflows and a devaluation of the exchange rate. The present paper develops a simple model where the exchange is crucial to analyze public debt dynamics. The paper also discusses the recent trajectory of the public debt in Latin America. The dynamics of the exchange rate is important for developing countries that do not have strong currencies and have a significant portion of public debt denominated in US dollars (original sin). Also, primary budget surpluses were crucial for the consistent and significant reduction of the public debt-to-GDP ratio. Hence, the economic expansion has created a larger fiscal space for Latin American economies to expand infrastructure and social spending, and reduce unemployment levels.
Keywords: F31; H60; O54; 330; Exchange Rate; Public Debt; Latin America